Supporting paper for the thesis Application of dynamic programming in capacity restraint assignment - Phaitoon Buddhamongkol (1976)
The study was undertaken to find out the feasibility of applying dynamic programming in capacity restraint assignment technique to a study area. It provided a computer program to estimate a realistic flow of transportation of each link in the study area. The work shows the advantages of the program over that of mathematical technique and classical calculus. Essentially, this study made use of multiple regression analysis. To increase the degree of relationship between the independent variables to that of the dependent variable, linear regression was used. The significance of the regression coefficient was tested using t-statistics. Based on the statistical analysis on the data, this study yielded the following findings and conclusions: 1. Dynamic programming in capacity restraint technique determined the suitable flow of transportation in these study area through the application of trip generation analysis, trip distribution, mode choice and trip assignment techniques. 2. Dynamic programming in capacity restraint assignment is more advantageous to use over that of mathematical technique and classical calculus for the following reasons: a. Dynamic programming can b4e used to reduce the number of calculations required. Savings in calculation time required becomes greater with large-sized problems. b. Dynamic programming approach has greater flexibility. It can be adjusted to fit different situations. c. With only a small number of additional calculations, the second, third, etc... best routes through a decision network can be located, thereby providing a measure of sensitivity that is often useful in many analyses. d. The amount of time to solve the subproblem at each stage is relatively constant for all stages. e. Complex problems are broken down into series of small problems and the resulting solutions are combined to arrive at a solution of a whole problem. On the basis of the findings in the study, the following recommendations are given: 1. The method is very useful for transportation planning. It must be recognized when planning present and future urban transport needs. The present understanding in this respect is still superficial and further study is required. 2. It is recommended that a greater framework be developed within which the technique can be placed in the wider context.3. Some techniques for analyzing travel behavior which have been used only on limited basis so far are utilized in the study. It is recommended that these be developed further and that their usefulness should be investigated more in actual transport studies. 4. Since the limiting factors such as the time, cost and manpower have somehow affected the result of the study in the selection of some variables used, (values used are from foreign and local studies made which can be used to apply in the study area) the researcher strongly recommends that real data be obtained and values established from it to facilitate a more accurate representation. 5. A grid structure approach form was devised by the researcher to present the approach. It is recommended that further research effort be applied to the possibility of devising other design than the grid structure such as a radial or circumferential form.
Supporting paper
Mimeographed
Thesis (M.S. ) --University of the Philippines Diliman.
Keywords: Dynamic programming; Transportation planning -- Philippines